Integrating Cultural Heritage through Oral Narratives: A Case Study in Uzbek Language Education - Rustambek Sharipov; Dildora Khodjaeva; Otabek Karimov (Yayasan Adra Karima Hubbi, 2025)
Background. The preservation and transmission of cultural heritage are critical components of language education, particularly in contexts where linguistic identity and oral tradition are closely intertwined. In Uzbekistan, oral narratives such as folktales, proverbs, and personal stories have historically served as vehicles for intergenerational knowledge and cultural continuity. Purpose. This study explores how integrating oral narratives into Uzbek language instruction can enhance cultural awareness, linguistic competence, and learner engagement. Method. Using a qualitative case study approach, the research was conducted in a secondary school in Tashkent with 26 ninth-grade students over a 10-week intervention. Data were collected through classroom observations, student reflections, teacher interviews, and narrative-based assignments. Results. The findings indicate that the use of oral narratives in language education fostered deeper connections between students and their cultural heritage, improved their expressive skills, and promoted collaborative learning. Students demonstrated increased motivation and identity affirmation when engaging with culturally embedded content. Conclusion. The study concludes that oral narratives are not only pedagogical tools but also cultural bridges that sustain linguistic and historical consciousness in the classroom. These results have implications for curriculum development and culturally responsive teaching in heritage language contexts.